The Monogamous family : a historical perspective - (:unkn) unknown (My University, 2015)
The reasons and consequences of the Catholic Church’s historical position on marriage among relatives since the 4th century have been extensively debated by many socio‐historians. The assertions made by Jack Goody that the Catholic Church’s position on Marriage among relatives was based merely on economic reasons, has been amply debated. Against Goody’s hypothesis history shows that during the early medieval age other Christian Churches and certain Jews proposed similar rules on marriage as the Catholic Church. On the other hand Christianity’s rebellion against religious preponderance of lineage has had a great influence on the advance of the said prohibitions.
The reasons and consequences of the Catholic Church’s historical position on marriage among relatives since the 4th century have been extensively debated by many socio‐historians. The assertions made by Jack Goody that the Catholic Church’s position on Marriage among relatives was based merely on economic reasons, has been amply debated. Against Goody’s hypothesis history shows that during the early medieval age other Christian Churches and certain Jews proposed similar rules on marriage as the Catholic Church. On the other hand Christianity’s rebellion against religious preponderance of lineage has had a great influence on the advance of the said prohibitions.
Keywords: Monogamy; Christian marriage; Eendogamy